TUKHTAMURODOV A.A. ERGONOMIC PRINCIPLES OF TEACHING PEDAGOGICAL SCIENCES WITH THE HELP OF COMPUTER PROGRAMS FOR FUTURE IT TEACHERS - Tokhtamurodov Azizbek Azimjon ugli (Journals Park Publishing, 2024)
The use of ergonomic studies and the training of future teachers of computer science, the factors for the effective use of computer programs in the study of pedagogy with the aim of convenient presentation of information using information technologies are highlighted. The issues of ensuring the work of a computer and its users with high motivation and minimal fatigue, the creation of optimal working conditions in terms of ergonomic design of human-computer interaction are considered.
Keywords: information technology, ergonomics, computer programs, ergonomic design, optimal working conditions, ergonomic educational environment.